Beyond the Digital: The Virtuality of the Flesh in Merleau-Ponty’s The Visibile and the Invisible - Ferro, Floriana (Scenari, 2024)
This paper aims to find, in Merleau-Ponty’s late thinking, a definition of the virtual which aligns with the latest advancements in digital technology while avoiding a reduction to the digital realm or a stark opposition to reality. The virtual is considered as a crucial characteristic in Merleau-Ponty’s late ontology, especially in The Visible and the Invisible, where a “virtual focus” or “virtual center” of the flesh is introduced. The argument posits that Merleau-Ponty’s monism of the flesh results in a dynamic view of virtuality, with significant ontological implications that reshape the relationship between the digital and the analogue. Merleau-Ponty’s concept of the virtual is defined by several key features: it applies to a monist perspective on reality, to a dynamic relationality between dialectic poles, and to the fabric of reality. This interpretation of the virtual implies a divergence from the digital, as virtuality belongs to the whole spectrum of reality.